Lung Function Changes with Swim Training in Healthy and Allergic Endurance Athletes - João Rodrigues; Bárbara Jesus; Paulo Caseiro; António Jorge Ferreira; Luís Rama (Journal of Functional Morphology and Kinesiology)
Background: It is thought that swimming might elicit remarkable chronic lung function improvements that were not observed in land-based sports. However, there is no consensus on whether this is mainly attributable to genetic predisposition or specific training. This study aimed to characterize athletes’ lung function according to their swimming experience. Methods: The sample consisted of 45 male athletes, including 15 swimmers, 15 triathletes, and 15 runners. Spirometry tests were conducted under four conditions: seated on land, prone on land, seated while immersed in water, and prone while immersed in water. The tests were performed on the pool deck and pool, with the order of conditions randomized for each participant. Conclusions: The results of this study do not support the idea that there is a window of opportunity for greater lung function adaptations during childhood due to swim training. The accumulated years of swim training are the reason for the increased measurements of FVC and FEV1 of swimmers. The immersed seated condition measures differences in lung function more accurately relative to swim training experience. Swim training appears to primarily enhance FVC in healthy athletes, while in allergic and asthmatic athletes, it mainly promotes improvements in FEV1/FVC and FEF25–75%.